PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA CV. MELLA VISTA PAMULANG - Akbar Satrio Nugroho; Sulaiman (Journal of Research and Publication Innovation, 2024)
This research aims to determine whether there is a positive and significant level of influence between price and service quality on CV consumer satisfaction. Mella Vista Pamulang. This research uses quantitative methods, the population is consumers who use products or services from CV. Mella Vista Pamulang, using incidental sampling which obtained 99 respondents. The data collection methods used were observation and questionnaires. The data analysis methods used are descriptive analysis and quantitative analysis, simple linear regression techniques, multiple linear regression, correlation coefficient (r), coefficient of determination (R square), partial hypothesis test (T test), simultaneous hypothesis test (F test). From the correlation analysis, it can be concluded that there is a very strong correlation between price and customer satisfaction, the correlation between service quality and customer satisfaction is very strong, the correlation between price and service quality and customer satisfaction is very strong. All three have a strong relationship with consumer satisfaction. From the results of the regression analysis, the multiple linear regression equation Y = -0.387 + 0.618 X1 + 0.269 X2 is obtained. From the hypothesis test and determination test, it shows that price simultaneously influences consumer satisfaction by 85.3%, while the remaining 14.7% is influenced by other factors or variables not examined in this research. Service quality simultaneously influences consumer satisfaction by 80.1% while the remaining 19.9% is influenced by other factors or variables not examined in this research. Price and service quality simultaneously have a significant influence on consumer satisfaction at CV. Mella Vista Pamulang was 86.5% while the remaining 13.5% was influenced by other factors or other variables.